A Facile and Diastereoselective access to Functionalised Benzopyrano[3, 4-a] Quinolizines via a Pyridine-Based Three-Component Reaction. (December 2017) - Esmaeili, Abbas Ali; Moradi, Abbas; Zangouei, Mahdieh; Fakhari, Ali Reza; Tabibi, Tooba
The reaction of 2-oxo-2 H -chromene-3-carbonitriles with dialkyl acetylenedicarboxylates and pyridines results in a three-component condensation reaction in which the 2-oxo-2 H -chromene-3-carbonitrile group acts as a dipolarophile to produce benzopyrano[3, 4- a ] quinolizines under mild conditions in good yield.